Transcriptomics and Proteomics Applied to Developmental Toxicology - Kultima, Kim (Uppsala universitet, Institutionen för farmaceutisk biovetenskap, 2007)
Developmental toxicology is an important part of preclinical drug toxicology as well as environmental toxicology. Assessing reproductive and developmental toxicity is especially expensive and time demanding, since at least two generations of animals are needed in the tests. In light of this there is a great need for alternative test methods in many areas of developmental toxicity testing. The complete set of RNA transcripts in any given organism is called the transcriptome. Proteomics refers to the study of the proteins in a given organism or cell population. The work of this thesis has focused on the use of high throughput screening methods in transcriptomics and proteomics to search for molecular markers of developmental toxicity. We have studied the global gene expression effects of the developmentally toxic substance valproic acid (VPA) using microarray technology. Several genes were found that display the same gene expression pattern in vivo using mouse embryos as the pattern seen in vitro using the embryocarcinoma cell line P19. Based on these observations, the gene Gja1 was suggested as one potential molecular marker of VPA induced developmental toxicity and potential marker of histone deacetylase (HDAC) inhibition in vitro. Using 2D-DIGE technology, which measures relative protein abundances, the effect of neonatal exposure to the flame retardant PBDE-99 was studied in mouse brain (cortex, hippocampus and striatum) 24 hr after exposure. Differentially expressed proteins in the cortex and the striatum indicate that PBDE-99 may alter neurite outgrowth. Finally, we have suggested several improvements in the use of the 2D-DIGE technology. Novel methods for normalizing data were presented, with several advantages compared to existing methods. We have presented a method named DEPPS that makes use of all identified proteins in a dataset to make comprehensive remarks about biological processes affected.